Global education through global Englishes / Afni Anida Adnan, Angeline Ranjethamoney Vijayarajoo and Sharina Salmi Azmi - Adnan, Afni Anida; Vijayarajoo, Angeline Ranjethamoney; Azmi, Sharina Salmi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Allow us to begin this article by telling you two stories, both that happened to two of us. The first, as relayed by the late father of one of us, took place back in the 70’s, when he was sent to Germany for a stint involving his work. One morning, as he was waiting for a bus, a friendly German chap approached him and said to him ‘How are you going’? My father found this odd- simply because both he and the German chap were at a bus stop-there was only one obvious mode of transportation. And so, despite feeling confused, my father answered, full of gusto, ‘by bus’, much to the amusement of the German man. One of us made a similar faux pas many years later, when she first arrived in Heathrow airport, London. What was even more ironic was that at that time, she was about to pursue an education degree, specializing in the Teaching of English as Second Language (TESL). Little did she know that she would be receiving her very first lesson in English just minutes after landing. She was actually in the midst of deliberately huffing out air in the crisp August morning while watching smoke form in full awe, when a burly British airport support staff walked up to her and asked. ‘Have you got the time, love?’ Panic gripped her and she took three steps back and eyed the man full of suspicion, and shot back to him, ‘For what?’